OCF, SALES GROWTH, DAN RASIO KEUANGAN LAINNYA YANG MEMENGARUHI FINANCIAL DISTRESS - KRISTIANTO, EVAN JEREMIA; BENY, BENY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to determine empirical evidence regarding the influence of operating cash flow, profitability, leverage, liquidity, sales growth, firm size, and institutional ownership on financial distress. The sample of this research is companies in the Food and Beverage Subsector which are listed consistently on the Indonesia Stock Exchange (BEI) during the period 2015 to 2022. This research method uses a purposive sampling method by obtaining 104 data from 13 companies listed consistently on the Indonesia Stock Exchange (IDX). This research was tested using multiple regression statistics. The result in this research showed that profitability, leverage, liquidity, and sales growth have an effect on financial distress, while the variables operating cash flow, firm size, and institutional ownership have no effect on financial distress.